2019
DOI: 10.4070/kcj.2018.0214
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab Treatment for Intravenous Immunoglobulin-resistant Kawasaki Disease: a Multicenter Study in Korea

Abstract: Background and ObjectivesWe investigated the status of infliximab use in intravenous immunoglobulin (IVIG)-resistant Kawasaki disease (KD) patients and the incidence of coronary artery aneurysms (CAAs) according to treatment regimens.MethodsBetween March 2010 and February 2017, 16 hospitals participated in this study. A total of 102 (32.3±19.9 months, 72 males) who received infliximab at any time after first IVIG treatment failure were enrolled. Data were retrospectively collected using a questionnaire.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Recently, Gyu Hur (17) and Nagatomo (10) in their retrospective study observed that the early administration of infliximab may reduce the incidence of significant CAA in patients with IVIG-resistant KD.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Gyu Hur (17) and Nagatomo (10) in their retrospective study observed that the early administration of infliximab may reduce the incidence of significant CAA in patients with IVIG-resistant KD.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have been published with remarkable results when anticytokine therapy is used in the treatment of KD. A meta-analysis regarding the effect of infliximab recently published has shown that use of infliximab in IVIG refractory patients has a very strong effect on decreasing the rate of coronary aneurysms with z-scores of >5 [6], while a previous study suggested that infliximab therapy may encourage early regression of aneurysms [7]. While clinical trials of IL-1 blockade are now ongoing [5], only case reports currently exist for use of anakinra for KD.…”
Section: Discussionmentioning
confidence: 99%
“…Specific blocking of TNF-α has been demonstrated to prevent coronary inflammation and the formation of CAA in mouse KD models induced by Lactobacillus casei cell wall extracts. In a previous study of a KD model in mice, it was indicated that a TNF-α anticoagulant can reduce the adhesion of neutrophils to vascular endothelial cells and the inflammation of arterial vascular endothelial cells (24,(39)(40)(41)(42). In the present meta-analysis, no significant differences in CAL, CAA, non-response rate, length of hospital stay, conjunctival injection or polymorphous exanthema between the two groups were observed; however, IFX or IFX plus IVIG significantly reduced the incidence of adverse events, the Table III.…”
Section: P-value N (Case/ ---------------------------------mentioning
confidence: 99%